2014
DOI: 10.1007/s00441-014-1935-4
|View full text |Cite
|
Sign up to set email alerts
|

NBCe1 (SLC4A4) a potential pH regulator in enamel organ cells during enamel development in the mouse

Abstract: During formation of dental enamel maturation-stage ameloblasts express ion-transporting transmembrane proteins. The SLC4 family of ion-transporters regulates intra- and extracellular pH in eukaryotic cells by co-transporting HCO3− with Na+. Mutation in SLC4A4 (coding for the Na+ bicarbonate co-transporter NBCe1) induces developmental defects in human and murine enamel. We hypothesized that NBCe1 in dental epithelium is engaged in neutralizing protons released during crystal formation in the enamel space. We im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 26 publications
7
50
0
2
Order By: Relevance
“…HAT‐7 cells are functionally polarized with high apical membrane CO 2 permeability and vigorous basolateral HCO3 uptake (Bori et al., ). This is similar to other HCO3‐secreting epithelia, such as guinea pig pancreatic duct (Ishiguro et al., ) and the human CFPAC pancreatic cell line (Rakonczay et al., ), and is consistent with the assumption that maturation‐stage ameloblasts are equipped with transporters to secrete HCO3 to neutralize the acidity generated during hydroxyapatite formation (Jalali et al., ; Lacruz et al., ; Smith, ). We also detected AE2 exchanger expression in HAT‐7 cells by immunocytochemistry, and its function was confirmed in Cl − substitution experiments by the inhibitory effect of 4,4′‐diisothiocyano‐2,2′‐stilbenedisulfonic acid) DIDS to block anion exchanger activity (Bori et al., ).…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By supporting
confidence: 82%
See 1 more Smart Citation
“…HAT‐7 cells are functionally polarized with high apical membrane CO 2 permeability and vigorous basolateral HCO3 uptake (Bori et al., ). This is similar to other HCO3‐secreting epithelia, such as guinea pig pancreatic duct (Ishiguro et al., ) and the human CFPAC pancreatic cell line (Rakonczay et al., ), and is consistent with the assumption that maturation‐stage ameloblasts are equipped with transporters to secrete HCO3 to neutralize the acidity generated during hydroxyapatite formation (Jalali et al., ; Lacruz et al., ; Smith, ). We also detected AE2 exchanger expression in HAT‐7 cells by immunocytochemistry, and its function was confirmed in Cl − substitution experiments by the inhibitory effect of 4,4′‐diisothiocyano‐2,2′‐stilbenedisulfonic acid) DIDS to block anion exchanger activity (Bori et al., ).…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By supporting
confidence: 82%
“…The two most likely pathways for basolateral HCO3 uptake in ameloblasts are by Na + ‐HCO3 cotransport and by CO 2 diffusion into the cells with carbonic anhydrase catalyzing its conversion into HCO3 ions and protons (Jalali et al., ; Lacruz et al., ). In HAT‐7 cells in the absence of HCO3/CO 2 , we identified a basolateral Na + dependent, amiloride sensitive proton extruding entity suggesting the presence of Na + /H + exchanger activity at this membrane (Racz et al., ).…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By mentioning
confidence: 99%
“…Located on the apical or basolateral membrane of polarized ameloblasts, NBCe1 and AE2 regulate intra-and extracellular pH by mediating the electrogenic transport of Na ϩ and bases (HCO 3 Ϫ and CO 3 2Ϫ ) (5). More recently, NBCe1 has been found in mouse dental epithelium and might be engaged in neutralizing protons released during crystal formation in the enamel space, thus regulating pH (53). In the current study, SLC4A4 and CFTR expression levels were significantly increased during human ameloblast differentiation, inversely linearly correlating with miR-224 expression.…”
Section: Discussionsupporting
confidence: 55%
“…The importance of a tight control of the extracellular pH on enamel mineralization has been previously emphasized . Mutations of SLC4 family bicarbonate transporters expressed by ameloblasts (eg, AE2 and NBCe1) result in altered enamel structure in mice and humans . Recent analyses have demonstrated that repeated pH cycling during the maturation stage allowed the progressive formation of enamel made of near‐perfect hydroxyapatite crystals .…”
Section: Discussionmentioning
confidence: 99%